Comparison of bioinformatics pipelines for eDNA metabarcoding data analysis of fish populations in Czech reservoirs - Dos Santos, Romulo Acácio (Jihočeská univerzita, 2021)
The aim of the study is a comparison of five distinct pipelines for environmental DNA (eDNA) metabarcoding using data collected in three reservoirs (Klíčava, Římov, and Žlutice) in the summer and autumn seasons. The results are analysed by comparing the number of reads assigned, number of species detected, and ecological indices (alpha and beta diversity). Finally, statistical analysis is applied to corroborate the results using analysis of variance (ANOVA), post-hoc Tukey, and permutational multivariate analysis of variance (PERMANOVA).
Comparison of bioinformatics pipelines for eDNA metabarcoding data analysis of fish populations in Czech reservoirs